PENGARUH WEIGHT TRAINING SISTEM SET DAN SISTEM CIRCUIT TERHADAP PENINGKATAN KEKUATAN OTOT LENGAN ATLET DAYUNG KABUPATEN AGAM - Achmad Raffy; Umar; Eri Barlian; Yendrizal (Fakultas Ilmu Keolahragaan Unimed, 2026)
This study aims to analyze the differences in the effects of set system and circuit system weight training on the increase in arm muscle strength of rowing athletes in Agam Regency. This study is an experimental study using a two-group pretest-posttest design, in which 12 rowing athletes were divided into two different treatment groups using purposive sampling techniques. The research instrument used a 1-minute pull-up test based on the Indonesian Physical Fitness Test (TKJI) to measure arm muscle strength. Data analysis was performed using a paired sample t-test at a significance level of α = 0.05 to determine the difference in ability before (pre-test) and after (post-test) treatment. The results showed that (1) the set system weight training significantly increased arm muscle strength (t-count 25.30 > t-table 2.02), (2) circuit training also had a significant effect on increasing arm muscle strength (t-count 10.83 > t-table 2.02), and (3) there was no significant difference in effect between the two training methods (t-count 1.19 < t-table 2.02).